2020
DOI: 10.1016/j.mex.2020.101084
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of supramolecular structure of Pluronic F127 micellar hydrogels using cryo-TEM

Abstract: Highlights Visualization of individual Pluronic® F127 micelles in hydrogels. Supramolecular structure evolution of micellar hydrogels as a function of concentration. Plunge-freezing of high viscosity solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…In addition, higher porosity is observed for OEGMA300 15 - b -BuMA 26 - b -DEGMA 13 (80.6 ± 0.5%) compared to the one of Pluronic F127 (72.2 ± 0.5%), which is essential for biomedical applications involving drug encapsulation and release and those that require efficient oxygen and nutrient transport through offering a high level of free void space. It is noteworthy that in the gel formed by Pluronic F127, the micelles are being organized, resulting in rows of micelles (Figure , bottom middle, and Figure S17) as previously observed …”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, higher porosity is observed for OEGMA300 15 - b -BuMA 26 - b -DEGMA 13 (80.6 ± 0.5%) compared to the one of Pluronic F127 (72.2 ± 0.5%), which is essential for biomedical applications involving drug encapsulation and release and those that require efficient oxygen and nutrient transport through offering a high level of free void space. It is noteworthy that in the gel formed by Pluronic F127, the micelles are being organized, resulting in rows of micelles (Figure , bottom middle, and Figure S17) as previously observed …”
Section: Resultssupporting
confidence: 75%
“…It is noteworthy that in the gel formed by Pluronic F127, the micelles are being organized, resulting in rows of micelles ( Figure 7 , bottom middle, and Figure S17 ) as previously observed. 88 …”
Section: Resultsmentioning
confidence: 99%
“…The 20% (w/v) PF concentration in P–S hydrogels is an adequate and widely used formulation for use as an injectable hydrogel [ 26 ]. At physiological temperature, the PF copolymer less than 15% (w/v) becomes a sol state and appears as a low-viscosity liquid; however, the 20% PF copolymer exists in a gel state [ 43 ]. When the concentration of PF is too high, side effects exist when used in the body [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The prepared formulation in the present study had a higher concentration than cmc (MP 1.0 :1.26 wt%, MP 5.0 : 6.30 wt%, MP 10 : 12.6 wt%, respectively, when dissolved in 10 mL), so the micellar structures were observed in cryo-TEM observations. NMR and SAXS results revealed that prepared MP formulations formed micellar structures, and SAXS observation results showed that FCC-packed micelles were obtained [29,30]. Pluronic ® F-127 has a triblock polymer with two hydrophilic tails in the structure.…”
Section: Discussionmentioning
confidence: 96%